Legal Protection for Women as Victims in the Criminal Action of Mugging in Medan City - Monica Sarah Sirait; Laris Perjuangan Tambunan; Yulkarnaini Siregar (IHSA Institute, 2023)
One of the crimes that is rife in the national news is the mugging that occurred in Medan City where women are often be victims.The purpose of thisis to find out the legal protection provided by the state to women as victims of criminal acts of mugging, especially in Medan City. This type of research is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive which explain the problem according to the research title. The data used is secondary data which consists of primary legal materials in the form of Law No. 31 of 2014 concerning amendments to Law No. 13 of 2006 concerning the protection of witnesses and victims, the Criminal Code, the Law No. 39 of 1999 concerning Human Rights, the Criminal Procedure Codeand secondary materials in the form of books, journals, electronic news, laws and regulations, court decisions and opinion of legal experts and writings related to the title of the research. Legal protection for women as victims of mugging in Medan City is urgently needed so that victims get justice. Law enforcers must unite to achieve an Integrated Criminal Justice System, especially the Police as law enforcers who have been given the authority by law to eradicate criminal acts of mugging that are rife in Medan City. Besides that, it is recommended for women to be more careful when driving at nightalone.